Pharmacokinetic Evaluation of CYP3A4‐Mediated Drug‐Drug Interactions of Isavuconazole With Rifampin, Ketoconazole, Midazolam, and Ethinyl Estradiol/Norethindrone in Healthy Adults. Issue 1 (25th July 2016) - Townsend, Robert; Dietz, Albert; Hale, Christine; Akhtar, Shahzad; Kowalski, Donna; Lademacher, Christopher; Lasseter, Kenneth; Pearlman, Helene; Rammelsberg, Diane; Schmitt‐Hoffmann, Anne; Yamazaki, Takao; Desai, Amit
Abstract: This report describes the phase 1 trials that evaluated the metabolism of the novel triazole antifungal isavuconazole by cytochrome P450 3A4 (CYP3A4) and isavuconazole's effects on CYP3A4‐mediated metabolism in healthy adults. Coadministration of oral isavuconazole (100 mg once daily) with oral rifampin (600 mg once daily; CYP3A4 inducer) decreased isavuconazole area under the concentration‐time curve (AUCτ ) during a dosing interval by 90% and maximum concentration (Cmax ) by 75%. Conversely, coadministration of isavuconazole (200 mg single dose) with oral ketoconazole (200 mg twice daily; CYP3A4 inhibitor) increased isavuconazole AUC from time 0 to infinity (AUC0‐∞ ) and Cmax by 422% and 9%, respectively. Isavuconazole was coadministered (200 mg 3 times daily for 2 days, then 200 mg once daily) with single doses of oral midazolam (3 mg; CYP3A4 substrate) or ethinyl estradiol/norethindrone (35 μg/1 mg; CYP3A4 substrate). Following coadministration, AUC0‐∞ increased 103% for midazolam, 8% for ethinyl estradiol, and 16% for norethindrone; Cmax increased by 72%, 14%, and 6%, respectively. Most adverse events were mild to moderate in intensity; there were no deaths, and serious adverse events and adverse events leading to study discontinuation were rare. These results indicate that isavuconazole is a sensitive substrate and moderate inhibitor of CYP3A4.